The development and validation literacy scale for pre-service mathematics teachers - Ying Zhou; Xiaofeng Lan (Annals of Mathematical Modeling, 2020)
The 21st century is an era in which education determines the future of society. The relevant theoretical research on core literacy is mainly carried out around students, and the research on the core literacy of pre-service mathematics teachers in ethnic areas has not yet begun. By consulting literature and existing mature questionnaires, combined with pre-service mathematics teachers' characteristics in ethnic areas, a "core literacy scale of pre-service mathematics teachers in ethnic areas" was compiled. Taking 412 pre-service mathematics teachers in Guangxi, China as the research object, using SPSS22.0 and AMOS24.0 to carry out project analysis, exploratory factor analysis, and confirmatory factor analysis on the data, the scale was revised accordingly, and the formal scale contains knowledge There are 3 dimensions of, ability, character, and the corresponding 9 factors. The scale compiled has good reliability and validity. It can be used as an effective tool to measure the core literacy of pre-service mathematics teachers in ethnic areas, and it also provides a basis for in-depth research on the current situation and strategies of training the core literacy of pre-service mathematics teachers in ethnic areas.